Multicellular convection flow in a cylindrical enclosure partitioned by a plate. (17th November 2019) - Wang, Yanping; Zhang, Wei
Abstract: This work performed a numerical investigation on the laminar natural convection in a cylindrical enclosure with a thin flat plate that is concentrically placed within the enclosure and is inclined with respect to the gravitational direction. The enclosure and plate are kept at low and high temperatures, respectively. The objective of this work is to explore the effects of the two geometrical parameters, i.e., the inclination angle and plate length, on the thermal and flow characteristics, with emphasis on the partitioning effect brought by the plate in generating the multicellular structures and weakening the intensities of fluid circulation and convection. The simulations were carried out using our in-house fourth-order finite difference code which is well validated in earlier studies. The effects of the two parameters are demonstrated by the variations of several characteristic quantities, including the overall heat transfer rate, temperature and stream-function distributions, spatial evolution of multiple vortices and local heat transfer pattern. Numerical results reveal that the inclined plate weakens the fluid circulation and lowers the heat transfer rate of the enclosure-plate system; the partitioning effect is strong for the long plate at nearly horizontal orientations. Depending on the magnitude of the two parameters, there can be at most three vortices within both the left and right halves of the enclosure, in which the primary vortices can be squeezed below the plate and the secondary or tertiary vortex occasionally emerges above the plate, and the thermal field is consequently determined especially in the top half of the enclosure. The spatial variation of the multiple vortices is greatly dependent on the two parameters, especially the two primary vortices. Finally, we observed that for a longer plate, the conduction in the gap between the end of plate and the enclosure becomes pronounced, as reflected by the magnitude and location of maximum local heat transfer rate on the enclosure surface.